PENGARUH PEMBERIAN SKIN ROLLING MYOFASCIAL RELEASE TERHADAP LOW BACK PAIN MYOGENIC PADA PEKERJA KONVEKSI - I Gede Gaura Chandra Lila Dasa; Arif Fadli; Yulianto Wahyono (Jurnal Nasional Fisioterapi, 2024)
Background: The most common health problem in convection workers is myogenic LBP. One intervention that can be given is SRMFR. Given SRMFR because the stimulus and pressure given from the skin will cause discomfort in the lower back pain will decrease. Purpose: to determine the effect of SRMFR on reducing myogenic LBP pain. Method: this research design uses an experimental one group pre test – post test design with control group conducted in June-July. The subject is a tailor who meets the inclusion criteria. The subjects numbered 30 people and were divided into 2 groups. The treatment group numbered 15 people given SRMFR and 15 people control group. Pain measurement using QVAS at the beginning and end of the study. Results: Based on the results of pre-post test statistical tests in the treatment group, a value of p = 0.000 (p < 0.05) was obtained, which means there is an influence. The results of the post-test hypothesis test between the treatment group and the control group obtained a result of p = 0.000 (p < 0.05) which means there is an influence. Conclusion: administration of SRMFR has an effect on reducing pain in myogenic LBP.